1990
DOI: 10.1148/radiology.175.1.2315473
|View full text |Cite
|
Sign up to set email alerts
|

Parietal pleural changes in empyema: appearances at CT.

Abstract: The parietal pleura bordering pleural space collections was analyzed with computed tomography (CT) in 35 patients with thoracic empyema, 30 patients with malignant effusion, and 20 patients with transudatory effusion. Enhancement of the parietal pleura was present in 96% of the 25 patients with empyema who underwent contrast material-enhanced examinations. Of the 35 patients with empyema, 86% showed thickening of the parietal pleura, 60% showed thickening of the extrapleural subcostal tissues, and 35% showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 0 publications
4
83
1
5
Order By: Relevance
“…Likewise, they observed pleural thickening only in exudative effusions with sensitivity of 42% and specificity 100%. Waite and colleagues [13] observed the same finding for pleural thickening in differentiating between exudative and transudative effusions. Aquino et al8 among 86 patients with pleural effusion, also observed pleural thickening only in one patient with transudative and 36 patients with exudative effusions with sensitivity of 61% and specificity of 96%.…”
Section: Discussionmentioning
confidence: 57%
“…Likewise, they observed pleural thickening only in exudative effusions with sensitivity of 42% and specificity 100%. Waite and colleagues [13] observed the same finding for pleural thickening in differentiating between exudative and transudative effusions. Aquino et al8 among 86 patients with pleural effusion, also observed pleural thickening only in one patient with transudative and 36 patients with exudative effusions with sensitivity of 61% and specificity of 96%.…”
Section: Discussionmentioning
confidence: 57%
“…It is vital to have adequate enhancement of the pathological pleura so that it can be seen in patients with empyema and malignant effusions [3,[8][9][10]. Waite et al [9] demonstrated that 96% of patients with empyema and up to 10% of patients with malignant effusions showed parietal pleural enhancement; 95% of the latter are metastatic in origin, with common primaries being lung and breast, while mesothelioma accounts for 5% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Waite et al [9] demonstrated that 96% of patients with empyema and up to 10% of patients with malignant effusions showed parietal pleural enhancement; 95% of the latter are metastatic in origin, with common primaries being lung and breast, while mesothelioma accounts for 5% [11]. Localised fibrous tumours involving the pleura also exhibit intense homogeneous contrast enhancement on CT [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible explanations for the higher prevalence of RPT reported by MARTINEZ et al [9]: 1) the patients had more severe illness compared with the present study; and 2) the patients were studied, for a second time, 3 rather than 6 months (as in the present study) after discharge. WAITE et al [12] evaluated the chest tomography scans in 35 patients with empyema within 2 weeks of a thoracentesis demonstrating an empyema. They reported only two from a total of 35 patients with RPT w5 mm.…”
Section: Discussionmentioning
confidence: 99%